2013
DOI: 10.1371/journal.pone.0062151
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against Phospholipase A2 Receptor in Korean Patients with Membranous Nephropathy

Abstract: The data were presented in abstract form at the 45th meeting of the American Society of Nephrology, October 30-November 04 2012, San Diego, CA, USA. Circulating autoantibodies against M-type phospholipase A2 receptor (PLA2R) are important pathogenic antibodies of idiopathic membranous nephropathy (MN) in adults. However, previous studies on the clinical impact of anti-PLA2R antibodies demonstrated several limitations, including insufficient numbers of study subjects and different time points and methods for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(128 citation statements)
references
References 31 publications
12
108
2
6
Order By: Relevance
“…The detection of circulating anti-PLA 2 R in a proteinuric subject is highly specific for the presence of primary MN on biopsy (24,39,40), and approximately 80% of patients with primary MN will be seropositive for anti-PLA 2 R when the disease first becomes clinically apparent (41)(42)(43)(44)(45). Small observational and retrospective studies have suggested a temporal relationship between anti-PLA 2 R and clinical disease activity.…”
Section: Anti-pla 2 R Autoantibodiesmentioning
confidence: 99%
“…The detection of circulating anti-PLA 2 R in a proteinuric subject is highly specific for the presence of primary MN on biopsy (24,39,40), and approximately 80% of patients with primary MN will be seropositive for anti-PLA 2 R when the disease first becomes clinically apparent (41)(42)(43)(44)(45). Small observational and retrospective studies have suggested a temporal relationship between anti-PLA 2 R and clinical disease activity.…”
Section: Anti-pla 2 R Autoantibodiesmentioning
confidence: 99%
“…2 The presence of anti-PLA2R1 autoantibodies has been widely confirmed in subsequent studies in 53%-80% of patients with iMN. [3][4][5][6] The pathogenic role of these autoantibodies is not yet proven, but anti-PLA2R1 antibody titers appear to correlate with disease activity in most study populations. However, the individual outcome prediction from anti-PLA2R1 titers is unclear.…”
mentioning
confidence: 99%
“…shown that, the antibody titres disappear with remission and reappear with disease relapses (8,13,14,17,18,(27)(28)(29)(30)(31)(32). Moreover, anti-PLA 2 R levels were in direct proportion to proteinuria and serum albumin levels.…”
Section: Discussionmentioning
confidence: 91%